Interplay between Lattice Distortions, Vibrations and Phase Stability in NbMoTaW High Entropy Alloys - Fritz Körmann; Marcel H.F. Sluiter (Entropy, 2016)
Refractory high entropy alloys (HEA), such as BCC NbMoTaW, represent a promising materials class for next-generation high-temperature applications, due to their extraordinary mechanical properties. A characteristic feature of HEAs is the formation of single-phase solid solutions. For BCC NbMoTaW, recent computational studies revealed, however, a B2(Mo,W;Nb,Ta)-ordering at ambient temperature. This ordering could impact many materials properties, such as thermodynamic, mechanical, or diffusion properties, and hence be of relevance for practical applications. In this work, we theoretically address how the B2-ordering impacts thermodynamic properties of BCC NbMoTaW and how the predicted ordering temperature itself is affected by vibrations, electronic excitations, lattice distortions, and relaxation energies.